Low bone mineral density is a prognostic factor for elderly patients with HCC undergoing TACE: results from a multicenter study - Müller, Lukas; Mähringer-Kunz, Aline; Auer, Timo Alexander; Fehrenbach, Uli; Gebauer, Bernhard; Haubold, Johannes; Theysohn, Jens; Kim, Moon-Sung; Kleesiek, Jens Philipp; Diallo, Thierno D.; Eisenblätter, Michel; Bettinger, Dominik; et al. (European radiology, 2023)
Low bone mineral density (BMD) was recently identified as a novel risk factor for patients with hepatocellular carcinoma (HCC). In this multicenter study, we aimed to validate the role of BMD as a prognostic factor for patients with HCC undergoing transarterial chemoembolization (TACE).
Online veröffentlicht: 20. August 2022
Gesehen am 03.05.2023